Kajian Yuridis Terhadap Perkawinan Beda Agama Setelah Keluarnya SEMA Nomor 2 Tahun 2023 Tentang Penolakan Permohonan Pencatatan Perkawinan Beda Agama - Suryati; Teguh Anindito; Aris Priyadi (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2024)
The aim of this research is to determine the impact of SEMA No. 2 of 2023 regarding the constitutional rights of people in interfaith marriages from the perspective of the principle of legal certainty. The trigger factor for the emergence of SEMA is because there is a legal loophole for couples who want to carry out an interfaith marriage, in Article 2 paragraph 1 of Law No. 1 of 1974 concerning Marriage, it is explained that to carry out a marriage they must adhere to their respective religious beliefs. In this article there is no explanation that interfaith marriages are prohibited, then the emergence of regulations regarding marriage registration in Article 35 letter a of the Population Administration Law explains in this article that marriages are carried out between religions. With this gap of uncertainty, the couple continued with an interfaith marriage, so the Supreme Court issued a circular for judges to reject the application for interfaith marriage and provide legal certainty.To achieve this goal, the author uses a normative juridical approach. The data used in this research is secondary data as the main data which includes primary legal material, secondary legal material and tertiary legal material. Data was analyzed qualitatively. Conclusion: the impact of the emergence of SEMA Number 2 of 2023 concerning rejection of requests for interfaith marriages, is a step to provide clarity on the confusion that occurs in society and as a guide for judges in rejecting requests for interfaith marriages. Then the emergence of SEMA gave rise to pros and cons in society. Rejection considers discrimination against personal rights in the context of marriage and limits the independence of judges in adjudicating trials. Keywords: Interfaith Marriage, SEMA Number 2 of 2023, Legal Certainty